IPv6- A new security challenge - Leitão, Vitor Manuel Carujo (2011)
IPv6 was developed to address the exhaustion of IPv4 addresses, but has not yet seen global deployment. Recent trends are now finally changing this picture and IPv6 is expected to take off soon. Contrary to the original, this new version of the Internet Protocol has security as a design goal, for example with its mandatory support for network layer security. However, due to the immaturity of the protocol and the complexity of the transition period, there are several security implications that have to be considered when deploying IPv6. In this project, our goal is to define a set of best practices for IPv6 Security that could be used by IT staff and network administrators within an Internet Service Provider. To this end, an assessment of some of the available security techniques for IPv6 will be made by means of a set of laboratory experiments using real equipment from an Internet Service Provider in Portugal. As the transition for IPv6 seems inevitable this work can help ISPs in understanding the threats that exist in IPv6 networks and some of the prophylactic measures available, by offering recommendations to protect internal as well as customers’ networks.